Macrophage Polarization in Physiological and Pathological Pregnancy - Yao, Yongli; Xu, Xiang-Hong; Jin, Liping (Frontiers in Immunology, 2019)
The immunology of pregnancy is complex and poorly defined. During the complex process of pregnancy, macrophages secrete many cytokines/chemokines and play pivotal roles in the maintenance of maternal-fetal tolerance. Here, we summarized the current knowledge of macrophage polarization and the mechanisms involved in physiological or pathological pregnancy processes, including miscarriage, preeclampsia, and preterm birth. Although current evidence provides a compelling argument that macrophages are important in pregnancy, our understanding of the roles and mechanisms of macrophages in pregnancy is still rudimentary. Since macrophages exhibit functional plasticity, they may be ideal targets for therapeutic manipulation during pathological pregnancy. Additional studies are needed to better define the functions and mechanisms of various macrophage subsets in both normal and pathological pregnancy.